Revisiting the ca. 845–820-Ma S-type granitic magmatism in the Jiangnan Orogen: new insights on the Neoproterozoic tectono-magmatic evolution of South China. Issue 4 (4th March 2019) - Deng, Teng; Xu, Deru; Chi, Guoxiang; Zhu, Yuhua; Wang, Zhilin; Chen, Genwen; Li, Zenghua; Zhang, Junling; Ye, Tingwei; Yu, Deshui
ABSTRACT: The Neoproterozoic tectonic evolution of the Jiangnan Orogen is controversial, with one of the issues being whether the ca. 850–820-Ma granitoids were generated by mantle plumes or the collision between the Yangtze and Cathaysia blocks. This paper tackles this problem by examining the age and petrogenesis of one of the granitoids, the Getengling pluton in the central Jiangnan Orogen, and through comparison with a regional geochronological–geochemical database compiled from previous studies. The Getengling pluton is characterized by high A/CNK values (~1.5), slight negative whole-rock ε Nd ( t ) values (−2.8 to −3.4), and positive zircon ε Hf ( t ) values (0.7 ± 1.1), suggesting S-type granite affinities with juvenile contributions. Rb/Sr, Rb/Ba, and high CaO/Na2 O ratios indicate psammitic sources with both clay-rich and clay-poor characters. These geochemical characteristics are distinct from those of the granitoids (typically of A type) associated with mantle plumes. The zircon laser ablation-inductively coupled plasma-mass spectrometry U–Pb age of 845 ± 4 Ma obtained in this study, together with other ca. 835–820 Ma ages of S-type granites in the Jiangnan Orogen, indicates that the felsic magmatism in the Jiangnan Orogen lasted for ca. 25 Ma, which is longer than typical plume-related felsic magmatism. In addition, the mafic rocks in the Jiangnan Orogen and elsewhere in the South China Block are geochemically distinct from the coeval mantle plume-related ones in Australia and west Laurentia. In geochemical diagrams diagnostic of tectonic settings, the Getengling pluton and other ca. 850–820 Ma intrusions plot in the syn- and post-collisional fields, whereas the pre-850 and post-820-Ma igneous rocks plot in the arc and within-plate settings, respectively. This sequential tectonic evolution from plate subduction through collision to within-plate environments further supports the hypothesis that the ca. 850–820-Ma granitoids in the Jiangnan Orogen resulted from the Yangtze–Cathaysia collision rather than from mantle pluming.